2016
DOI: 10.5038/2640-6489.1.1.1000
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting medical tourism destination selection: A Malaysian perspective

Abstract: The study aims to assess the factors for medical tourism destination selection from medical tourist's perspective and to determine the satisfaction level of medical tourists in Malaysia. Field survey was conducted with the structured questionnaire to medical tourists admitted at 11 public and private hospitals in Kuala Lumpur region during September and October, 2013. A nonprobability convenience sampling technique was used and 72 response were collected. Geography of Malaysia was found to be an important fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 9 publications
0
23
0
1
Order By: Relevance
“…Many studies have demonstrated that medical facilities' savings, revenue and market share are directly affected by high service standards (Chiou and Droge, 2006;Becerril-Arreola et al, 2017;Burkle et al, 2017;Tartaglione et al, 2018. Kumar andHussian, 2016). Kuala Lumpur's healthcare sector was assessed by Kumar and Hussain (2016) in terms of variables enticing medical tourism, with patients' satisfaction found to be beneficially and directly influenced by Malaysia's geography and other country-specific conditions, as well as institutional efficacy in Kuala Lumpur, among various other factors influencing health tourists' choices.…”
Section: The Study Gapmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have demonstrated that medical facilities' savings, revenue and market share are directly affected by high service standards (Chiou and Droge, 2006;Becerril-Arreola et al, 2017;Burkle et al, 2017;Tartaglione et al, 2018. Kumar andHussian, 2016). Kuala Lumpur's healthcare sector was assessed by Kumar and Hussain (2016) in terms of variables enticing medical tourism, with patients' satisfaction found to be beneficially and directly influenced by Malaysia's geography and other country-specific conditions, as well as institutional efficacy in Kuala Lumpur, among various other factors influencing health tourists' choices.…”
Section: The Study Gapmentioning
confidence: 99%
“…They found that the strong customer service, lower expenditure and high standards are the most significant reasons. Others studies have analysed more the variables affecting health tourism distention choice across various countries (Kumar and Hussian, 2016;Rezaee and Mohammadzadeh, 2016). Alsarayreh et al (2017), therefore, recommended to use modern technological ways in marketing Jordanian HSOs in a foreign country and to reassess the price with other competitive counties and to use more clear information to promote Jordan as a convenient medical tourism destination.…”
Section: The Study Gapmentioning
confidence: 99%
“…Security can be viewed as an indispensable condition for travel tourism, especially in this era of global tourism (Kovari & Zimanyi, 2011). Reinforcing security in a tourist location will likely have the effect of providing a low perception of risk by tourists in a tourist location (Kumar & Hussian, 2016). Though, expectations of tourists regarding a security location also influence their evaluations of risk.…”
Section: Rationale For Expectations In the Destination Security Perspmentioning
confidence: 99%
“…Several studies have revealed that individuals seeking treatments overseas have had unsatisfactory experiences in health services provided by the city's medical staff, especially for internal, cardiac, and obstetrics and gynecology (Ob-Gyn) diseases [4], [5], [6], [7]. This is an indicator of the low quality of health services in Medan City [8], [9], [10], [11], [12], [13].…”
Section: Introductionmentioning
confidence: 99%